Recent developments in the ordered weighted averaging operators theory and practice - Kacprzyk, Janusz; Beliakov, Gleb.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This volume presents the state of the art of new developments, and some interesting and relevant applications of the OWA (ordered weighted averaging) operators. The OWA operators were introduced in the early 1980s by Ronald R. Yager as a conceptually and numerically simple, easily implementable, yet extremely powerful general aggregation operator. That simplicity,  generality and implementability of the OWA operators, combined with their intuitive appeal, have triggered much research both in the foundations and extensions of the OWA operators,  and in their applications to a wide variety of problems in various fields of science and technology. Part I: Methods includes papers on theoretical foundations of OWA operators and their extensions.The papers in Part II: Applications show some more relevant applications of the OWA operators, mostly means, as powerful yet general aggregation operators. The application areas are exemplified by environmental modeling, social networks, image analysis, financial decision making and water resource management.
Part I: Methods -- OWA Operators and Nonadditive Integrals -- The WOWA Operator: A Review --  Induced Ordered Weighted Averaging Operators -- A review of the OWA determination methods: classification and some extensions -- Spezification of the OWA Operators for Aggregating Uncertain Information with Uncertain Weights -- A majority guided aggregation operator in group decision making Generating OWA Weights from Individual Assessments -- The role of the OWA operators as a unification tool for the representation of collective choice sets -- Applying linguistic OWA operators in consensus models under unbalanced linguistic information -- Part II: Applications -- Fusion Strategies based on the OWA Operator in Environmental Applications -- Decision Making with Dempster-Shafer Theory using Fuzzy Induced Aggregation Operators -- Two methods for image compression/reconstruction using OWA operators -- OWA-based fuzzy m-ary adjacency relations in Social Network Analysis -- Soft Computing in Water Resources Management by Using OWA Operator -- Combination of Similarity Measures in Ontology Matching using the OWA Operator.
Electronic reproduction.
Keywords: Aggregation operators; Electronic books